Estudos prospectivos sobre o ciber terrorismo na Paraíba - Silva, José Roberto Cavalcante da (2018)
Information has acquired the status of asset in public or private organizations in the information society. It is perceived that the use of information and communication technologies by institutions has potentiated and increased its competitiveness, providing speed and celerity of transmission and information processing. Likewise, threats to information security stand out as more sophisticated forms of attacks on information assets, such as cyber-terrorism, the subject of this study, emerge. This research aimed to prospect scenarios about cyber terrorism in Paraíba. Public agencies and companies that have suffered attacks or threats of attacks described in the media as cyber terrorism from January 2016 to 2017 have been consulted as an intentional sample for the convenience of the research. For this, an investigation of qualitative and quantitative nature, bibliographical and descriptive, was carried out, using Godet's method of prospective scenarios. At the data analysis stage, the instruments used were: structural analysis; Actors Method, Objectives, Strength Relationships; and morphological analysis. These tools are specific to Godet's method, which is aided by software. As a result, a diagnosis of the information security and cyber-terrorism situation in Paraíba organizations was presented. The following variables were identified: public policies; ideologies; market; technologies and undue advantage. Also, the following actors were pointed out: government; companies; contributors; customers / users and external people. Finally, the following possible scenarios for cyber terrorism in Paraíba were developed: a favorable scenario; adverse scenario; and probable scenario. The first one was exposed as a favorable scenario for the accomplishment of attacks of cyber terrorist nature within the organizations studied. The second was presented as an unfavorable scenario for cyber terrorism in the analyzed context. The third shows a gradual increase in cyber terrorist attacks in the conjuncture of the investigated institutions.